Variable amplitude loading of spray‐formed hypereutectic aluminium silicon alloy DISPAL® S232 in the VHCF regime. (19th March 2014) - Fitzka, M.; Mayer, H.; Schuller, R.; Stanzl‐Tschegg, S. E.; Przeorski, T.; Krug, P.
ABSTRACT Spray‐formed hypereutectic aluminium silicon alloy DISPAL® S232–T6x is cycled with variable amplitude at ultrasonic frequency up to the very high cycle fatigue (VHCF) regime under fully reversed tension–compression loading. The Powder Metallurgy alloy is tested using a Gaussian cumulative frequency distribution of load cycles, and lifetimes are compared with constant amplitude data. Miner calculation delivers mean damage sums between 0.5 and 0.9 for mean lifetimes between 8 × 107 and 1.6 × 1010 cycles, respectively. Cracks are initiated at voids, at inclusions or at distributed inhomogeneities (porous areas or oxides) at the surface or in the interior. In situ analysis of vibration properties indicates that cracks are formed and start growing from the beginning of fatigue cycling, even if failure occurs in the very high cycle fatigue regime. Crack initiation stage is negligible. Lifetime prediction calculation is performed using an adapted Paris‐law and considering lifetime as cycles necessary to propagate an initial crack to failure. Measured and predicted mean lifetimes differ by factor 0.4–1.0. Large crack‐initiating defects strongly reduce the fatigue lifetimes, which is successfully covered in the crack propagation model.